An efficient design methodology for graded surface-based lattice structures using free-size optimization and enhanced mapping method - Ugur Simsek; Mirhan Ozdemir; Polat Sendur (Materials & Design, 2021)
In this paper, a novel Free-size Optimization based Graded Lattice Generation (FOGLG) method, that generates the functionally graded lattice (FGL) structures using free-size optimization, is proposed. In addition, the reconstruction method suitable for the construction of 3D FGL structures using Additive Manufacturing (AM) is presented. The proposed method employs the thickness information of each shell element obtained from a free-size optimization algorithm to determine the relative element densities, which collectively represent the set of design parameters. An additive manufacturing compatible mapping method of generating FGLs from 2D free-size optimization results is also proposed. The efficiency of the FOGLG was compared to the existing homogenization-based optimization (HMTO) and size optimization algorithms. The objective function of the three optimization strategies targets to minimize the total acceleration spectrum in the frequency range of interest. The effectiveness and validity of this new design method was also demonstrated from laser vibrometer measurements. The results show that the FOGLG reduces the overall acceleration spectrum by 3.6% and 19.4% compared to the HMTO and size optimization algorithms, respectively. High correlation between the numerical and experimental results validates the effectiveness of the proposed algorithm.